Room temperature monitoring of SF6 decomposition byproduct SO2F2 based on TiO2/NiSO4 composite nanofibers. (5th May 2021) - Li, Li; Din, Salah Ud; ul Haq, Mahmood; Tang, Nian; Zhang, Manjun; Rahman, Nasir; Zhu, Liping
Abstract: Sulfuryl fluoride (SO2 F2 ) is one of the ideal decomposition components of sulfur hexafluoride (SF6 ), which is widely used as an insulating and arc extinguishing medium in gas-insulated switchgear. To detect the decomposition component of SF6 at room temperature, the use of SO2 F2 is still a challenge. In this work, we have successfully fabricated TiO2 nanofibers and nickel sulfate (NiSO4 NPs) via simple electrospun and hydrothermal methods, followed by calcination process to improve the sensing performance. Metal oxide semiconductor materials (MOSs) are widely used in gas sensing applications due to their superior performance and fast recovery speed. Although the performance of our TiO2 /NiSO4 composite nanofiber sensor decreases at higher temperatures, it shows an excellent response to target gasses at room temperature. Ni-decoration on the outer surface of the nanofibers could maximize the sensing response of 100 ppm SO2 F2 by up to 189% at room temperature, showing that the TiO2 /NiSO4 composite nanofibers are 2.5 times superior to the pure TiO2 nanofiber sensors. Thus, the approach for this novel composite nanofiber-based material is promising for the fabrication of superior gas sensors for decomposition of SF6 .